2021
DOI: 10.1177/02698811211026456
|View full text |Cite
|
Sign up to set email alerts
|

High dose antipsychotic polypharmacy and dopamine partial agonists - time to rethink guidelines?

Abstract: Guidelines for the treatment of schizophrenia limit the use of antipsychotic agents to clinically-established maximum doses. This acknowledges both the absence of additional efficacy of dopamine D2 receptor antagonists above a receptor occupancy threshold, and the increases in side effects that can occur at higher doses. These limits restrict the dosing of combinations of antipsychotics as they do single agents; drugs sharing the major antipsychotic mechanism of D2 receptor antagonism will act additively in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…In this regard, a systematic review and meta-analysis of randomized controlled trials comparing APP and monotherapy found no differences regarding intolerability-related treatment discontinuation ( 4 ). Moreover, again attesting to the above, it is more likely that APP strategies involving a greater total antipsychotic dose, and thus net target (e.g., D2 receptor) occupancy ( 8 )—at least by antagonist agents [see, e.g., ( 19 )]—would be more liable to increase the AE burden. Conversely, therapeutically useful effects on AE outcome may be achieved by partial DA agonist add-on to CLZ, RIS, OLA, or HAL, to relieve metabolic- and prolactin (PRL)-derived issues ( vide infra ).…”
Section: App: Why When and To Whom?mentioning
confidence: 95%
“…In this regard, a systematic review and meta-analysis of randomized controlled trials comparing APP and monotherapy found no differences regarding intolerability-related treatment discontinuation ( 4 ). Moreover, again attesting to the above, it is more likely that APP strategies involving a greater total antipsychotic dose, and thus net target (e.g., D2 receptor) occupancy ( 8 )—at least by antagonist agents [see, e.g., ( 19 )]—would be more liable to increase the AE burden. Conversely, therapeutically useful effects on AE outcome may be achieved by partial DA agonist add-on to CLZ, RIS, OLA, or HAL, to relieve metabolic- and prolactin (PRL)-derived issues ( vide infra ).…”
Section: App: Why When and To Whom?mentioning
confidence: 95%
“…The antipsychotics most commonly combined with aripiprazole are clozapine and olanzapine, but only the combination with clozapine has shown greater effectiveness in preventing hospital admission than the antagonist (clozapine) alone in naturalistic studies (Tiihonen 2019); this may reflect better adherence to medication when side-effects such as weight gain are addressed. Such uses have – in contrast to the combination of full antagonists – a possible theoretical basis (Reynolds 2021).…”
Section: Learning Objectivesmentioning
confidence: 99%
“…Bipolar disorder treatment frequently requires antipsychotics, but monotherapy, despite being suggested by guidelines (Taylor et al , 2021), is often less common than polytherapy in clinical practice, though with a large variability across centers (Dell’Osso et al , 2020). Polytherapy may be useful in some specific cases (Lähteenvuo and Tiihonen, 2021); however, the combination of full dopamine D2 receptor agonists with partial agonists is debated, given the scarce evidence available (Reynolds, 2021).…”
mentioning
confidence: 99%